The Relationship Between Student Motivation and Participation Level in Mountain Climbing as a Recreational Sport - Raka Maulana Malik; Muhammad Nur Alif; Rizal Ahmad Fauzi (Journal Coaching Education Sports, 2026)
Mountain climbing as a recreational sport has become increasingly popular among university students. However, participation levels remain varied, indicating the need to examine psychological factors influencing student involvement, particularly motivation. This study aimed to analyze students’ motivation levels, participation levels, and the relationship between the two variables in mountain climbing activities. A quantitative correlational design was employed involving 30 members of the Nature Lovers Student Activity Unit at the Indonesian University of Education, Sumedang Campus. Data were collected using the Intrinsic Motivation Inventory (IMI) questionnaire and a participation questionnaire based on Keith Davis’s participation theory. The findings showed that most students had high motivation (83.3%) and high participation levels (83.3%). Pearson correlation analysis revealed a strong positive relationship between student motivation and participation level (r = 0.776, p < 0.01). These findings indicate that higher student motivation is associated with greater participation in mountain climbing activities. This study highlights the importance of strengthening intrinsic motivation through structured recreational sport programs to promote sustainable student participation.